Śrī Netramaṇibhāīne lakhelā aṅgata patrono saṅgraha - Kalelkar, Dattatraya Balakrishna, 1885- (SAMP early 20th-century Indian books project ;, 1947)
Collection of the author's letters to Netramaṇibhāī Śropha, 1883?-1941, a person disabled by prolonged illness.